Pengaruh Kredibilitas Influencer dan Consumer Review Terhadap Minat Beli Produk Ms Glow pada Platform Shopee - Muhamat Hasyim Fahmi Midrorun Niami; Imronudin (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This research aims to analyze the influence of influencer credibility and consumer reviews on buying interest. The sampling method was purposive sampling technique. The questionnaires were distributed via buying online to 100 respondents.The collected date were analysed using Partial Least Square (PLS) . The results show that both the influencer credibility and consumer review variables are positive and significant influence on buying interest in MS Glow products on the Shopee platform. Has the highest influence on buying interest.